Emerging Virus Diseases - Burrell, Christopher J. (Fenner and White's Medical Virology, 2017)
Emerging viral diseases now represent a major concern worldwide with the appearance of a new virus, or the re-emergence of a previously recognized virus with altered epidemiology and properties, occurring almost annually. Prominent examples in the last years include the sudden crossing of H5N1 avian influenza virus into humans in 1995, the unexpected West African outbreak of Ebola virus in 2014, the appearance of the Middle East respiratory syndrome related to the SARS virus first recognized in 2003, and the more recent epidemic of Zika virus in the Americas. These are just a few examples representing the constantly evolving relationship between pathogen and host, a process of evolution accelerated by population growth, climatic changes, and human activities.